PENGARUH LEADER MEMBER EXCHANGE (LMX) TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) UNIT REKAM MEDIS DI RSUD dr. HASRI AINUN HABIBIE - Ayudhita Cahyani Daud; Lilis Handayani (Jurnal Infokes, 2023)
Leader Member Exchange (LMX) can influence employees so that they can demonstrate Organizational Citizenship Behavior (OCB) which is believed to increase productivity and creativity in work units. This study aims to determine the Effect of Leader Member Exchange (LMX) on Organizational Citizenship Behavior (OCB) Unit Medical Records at RSUD dr. Hasri Ainun Habibie. This study is a quantitative study using an analytical observational design with a cross sectional approach. The population in this study were all medical record officers at RSUD dr. Hasri Ainun Habibie, totaling 30 medical record officers. In this study using a questionnaire and the data tested using Spearman correlation. The results of this study indicate that there is an effect of Leader Member Exchange (LMX) on Organizational Citizenship Behavior (OCB) with the results of the Spearman correlation test, namely p = 0.021 (<0.05) with a large correlation value of 0.419 which is categorized as strong enough, which means that the higher the LMX, the higher the LMX. the higher the OCB of medical records in RSUD dr. Hasri Ainun Habibie.